Legislative proposal in Italy to facilitate contacts between deceased organ donor families and transplant recipients - De Santo, Natale Gaspare; Cirillo, Massimo; De Santo, Luca S; Abbas, Mohamed Hamed; De Rosa, Giusy; Resic, Halima; Perna, Alessandra F; Spasovski, Goce; Citterio, Franco; Venditti, Guglielmo; Balat, Ayse; Santini, Luigi; et al. (Springer Science and Business Media LLC, 2020)
Contacts between organ donors and recipients might be possible in the near future in Italy. As suggested by The Italian Committee of Bioethics "anonymity is requested by the Italian National Transplant Centre" before transplantation anonymity shall be strict in order to grant privacy, gratuity, justice, solidarity and benefits and avoids organ trafficking. Following a period that is ethically correct and justifiable, organ donor families and recipients can meet after signing a valid declaration of consent, expressed on a template valid for the whole country. A third party within the body of the National Health Systems shall control the validity of the consent. The opinion stresses that contacts are not a right but a possibility justifiable on ethical grounds if the procedure is followed appropriately. A legislative proposal has been presented before the Chamber of deputies incorporating all suggestions made by the National Committee of Bioethics. The agreement between parties might be signed a year after transplantation. This is a long enough period of time for the recipients to fully appreciate the benefits of the procedure and for the donor families to see the effects of their decision (the opinion and the Law proposal hit the Zeitgeist, and keep Italy in the regulation of European Union).